Modeling & transient analysis of DFIG based wind farm - Nagendra Kumar, S.; Suman Poul Reddy, T.; Nagaraju, A.; Narsi Reddy, V.; Veerendranath, K.; S. Hareesh, S.; Chaithanya, S.; Krishnarjuna Rao, S. (International Journal of Engineering and Technology, 2018)
This manuscript presents the modeling and simulation studies of grid connected Doubly Fed Induction Generator (DFIG) based wind farm. In current scenario, DFIG is used for the large scale wind energy systems. DFIG is high sensitive for the faults on the system due to termi-nals of stator directly fed to the grid. In this work the dynamic response of the proposed system under varying wind speeds and three transi-ent faults at different locations for different durations are studied.Â